Innovation power: Why technology will define the future of geopolitics - Schmidt, Eric (Foreign Affairs)
When Russian forces marched on Kyiv in February 2022, few thought Ukraine could survive. Russia had more than twice as many soldiers as Ukraine. Its military budget was more than ten times as large. The U.S. intelligence community estimated that Kyiv would fall within one to two weeks at most.- Reproduced